2001
DOI: 10.4049/jimmunol.167.9.4942
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Nicotinamide Adenine Dinucleotide Induces T Cell Apoptosis In Vivo and In Vitro

Abstract: Incubation of mouse T cells expressing the cell surface enzyme ADP ribosyltransferase with nicotinamide adenine dinucleotide (NAD) had been reported to cause ADP ribosylation of cell surface molecules, inhibition of transmembrane signaling, and suppression of immune responses. In this study, we analyze the reasons for these effects and report that contact of T cells with NAD causes cell death. Naive T cells when incubated with NAD and adoptively transferred into semiallogeneic mice fail to cause graft-vs-host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 35 publications
2
43
1
Order By: Relevance
“…Treating naive T cells with NAD before injection into semiallogeneic mice blocks induction of graft-vs-host disease (2). Treating T cells before injection into syngeneic mice blocks their migration to the spleen and directs them to the liver where they appear to die (2).…”
Section: T He Addition Of Nad To Murine T Lymphocytes Inhibits Their mentioning
confidence: 99%
“…Treating naive T cells with NAD before injection into semiallogeneic mice blocks induction of graft-vs-host disease (2). Treating T cells before injection into syngeneic mice blocks their migration to the spleen and directs them to the liver where they appear to die (2).…”
Section: T He Addition Of Nad To Murine T Lymphocytes Inhibits Their mentioning
confidence: 99%
“…ART2-mediated modification of surface proteins would thus have an inhibitory effect on the expansion of T cell responses. As previously mentioned, NAD+ was shown to induce T cell apoptosis [5]. This was demonstrated to be an ART2-dependent mechanism [33,36].…”
Section: Art2mentioning
confidence: 74%
“…Recently it has been shown that a significant level of NAD+ is present in exudates during the early phase of the inflammatory response and that this concentration is sufficient to provoke NAD+-induced T cell death (NICD) in vitro [4]. Injection of NAD+ into wild type mice induces massive depletion of T cells [4,5] confirming the inhibitory function of NAD+ in T cell proliferation and cytotoxic activity in vitro [5]. It has been demonstrated by Seman et al [6] that NAD+ selectively induces apoptosis of mouse T cells (both CD4+ and CD8+) but not B cells.…”
Section: Introductionmentioning
confidence: 99%
“…Human monocytes basally express ART3 mRNA and inducibly express ART4 mRNA in response to LPS priming [35,36]; however, neither ART3 nor ART4 appear to act as functionally active ADPribosyltransferases. As noted previously, the expression and function of the ART2 gene products have been extensively characterized in murine T cells [9,17,33,37] and we recently reported that ART2.1 is selectively expressed in murine BMDM stimulated with IFNs or LPS [16]. These new data conclusively demonstrate that ART2.1 is expressed as a functional ecto-enzyme in a much broader range of leukocyte subtypes (dendritic cells, macrophages, B cells, and T cells) than is ART2.2 which appears restricted to T cell subsets.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, freshly isolated T cells from the same mice basally express both ART2.1 and ART2.2 [17][18][19][20][21][22][23]. Given these striking differences in expression of ART2.1 and ART2.2 in different leukocyte subsets and under in vivo versus in vitro conditions, this study was designed to address two major questions: (1) Is ART2.1 is expressed in leukocyte types other than macrophages and T cells?…”
Section: Introductionmentioning
confidence: 99%